Active Filter Analysis on Designing Electronic Stethoscope - Prihatin Oktivasari; Riandini Riandini; Rahmah A. Fitri; Sungguh I. Malaon (National Research and Innovation Agency, 2019)
Early heart disease detection could be vital and some other diagnostic ways are being developed. In this paper, a lowcost tool for a diagnostic that analyzes the digitized heartbeat sound is given. This can be used to detect heart anomalies. The instrument shows the heart sound and also keeps a patient's long-term record for future use. The signal from the heart provides a lot of knowledge about the heart and offers an initial diagnosis recommendation. The electronic stethoscope uses the condenser microphone, preamplifier circuit, and filter circuit. The optimum filter is Butterworth with a fourth-order Sallen key low pass filter topology with a gain of 0.707 volts, -3.01 dB, and a fourth-order high pass filter with a gain of 0.782 volts, -2.137 dB. The frequency of the heart sound is about 20 Hz – 120 Hz in general. Therefore, the lower cutoff frequency of the filter is set to 20 Hz, while the higher cutoff frequency set to 120 Hz. The evaluation used to measure the performance of an electronic stethoscope is to compare with a conventional stethoscope, the recorded sound is the same.